2022
DOI: 10.3390/jcm11041110
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Sedentary Time in Patients with COVID-19 after Hospitalisation

Abstract: Many patients with COVID-19 experience severe and even fatal disease. Survivors may have long-term health consequences, but data on physical activity and sedentary behaviour are scarce. Therefore, we objectively assessed physical activity (PA) patterns among post-hospitalised patients with COVID-19 and explored associations with patient characteristics, disease severity and cardiac dysfunction. We objectively assessed PA, sedentary behaviour and sleep duration for 24 h/day during 8 days at 3-6 months after COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
4
6
0
Order By: Relevance
“…As this observation is not statistically signi cant further research with a longer follow-up-interval is needed to con rm this result. Regarding the age of the participants, the current results are consistent with the results of van Bakel, et al (30). Younger post-COVID patients (<55 years) tend to spend less time inactive and achieved a signi cantly higher amount of vigorous PA before rehabilitation compared to older patients (≥55 years).…”
Section: Physical Activitysupporting
confidence: 91%
See 3 more Smart Citations
“…As this observation is not statistically signi cant further research with a longer follow-up-interval is needed to con rm this result. Regarding the age of the participants, the current results are consistent with the results of van Bakel, et al (30). Younger post-COVID patients (<55 years) tend to spend less time inactive and achieved a signi cantly higher amount of vigorous PA before rehabilitation compared to older patients (≥55 years).…”
Section: Physical Activitysupporting
confidence: 91%
“…Plekhanova, et al (29) reported a lower amount of MVPA with mean (M) = 14.9 minutes/day of female and M = 21.1 minutes/day of male post-COVID patients, which is below the recommended PA level. The female and male patients spend M = 12.1 to 12.6 hours/day in an inactive state, which is in line with ndings by van Bakel, et al (30). The authors of the mentioned studies compared their results with these of healthy population studies and stated, that post-COVID patients are less physical active, and thus, PA should be promoted within this patient cluster.…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…In addition, during autopsies of patients who died with COVID-19, a high burden of microvascular thrombosis was found as well as macrovascular thromboembolic events that were clinically unsuspected before death ( 17 , 18 ). Many patients hospitalized with COVID-19 also had additional risk factors for VTE and were likely to be more sedentary after hospital discharge ( 19 ). On the basis of these observations, we estimated the primary end point rate would be 4% in the placebo-treated participants by day 30 after hospital discharge.…”
Section: Discussionmentioning
confidence: 99%